Voucher specimens matter! Confirmation of Lecanorchis multiflora (Vanilloideae) in the tropical rainforest of the Philippines with notes on its habitat and conservation status - Naive, Mark Arcebal K. (2022)
Lecanorchis multiflora (Orchidaceae) was recently collected in Mt. Timolan Protected Landscape, province of Zamboanga del Sur, in the Philippine archipelago. This is the first record of the species with a voucher specimen in the Philippines. A description based on our recent collection, colour photographs to aid identification, geographic distribution information, ecology, phenology, and IUCN conservation assessment are provided below.